REVITALISASI FUNGSI BAITUL MAAL: STUDI KOMPARATIF PENGELOLAAN ZISWAF ERA RASULULLAH SAW., DAN MASJID JOGOKARIYAN - Nea Sasgapata Kurniawan, Anugallakata; Mawadah, Sokhikhatul; Anwar, Khoirul (Program Studi Magister Ekonomi Syariah UIN Ar-Raniry, 2026)
The phenomenon of modern mosque management, which tends to be oriented toward cash balance accumulation (saving oriented), contradicts the practice of baitulmal in early Islam, which emphasized high liquidity for the rapid resolution of social problems. This study aims to analyze the revitalization of the baitulmal function through the implementation of the “Zero Balance” strategy at the Jogokariyan Mosque in Yogyakarta. Using a qualitative approach with a descriptive-comparative case study method, this study compares field data from interviews and observations with classical Islamic historical literature, particularly the book Al-Amwal by Abu Ubaid. The results of the study show that: (1) The application of the “Zero Balance” philosophy is a contemporary manifestation of the principle of fauriyah (immediate distribution) which rejects the hoarding of entrusted assets in order to maintain the economic circulation of the community; (2) The “Spearhead and Spearpoint” leadership strategy is effective in building strong social trust through the exemplary sacrifice of personal wealth by administrators, as practiced by the Companions; and (3) The transformation of the distribution pattern from consumptive assistance to productive empowerment (fiqh al-tamkin) is realized through an interest-free business capital scheme and operational independence support from the Mosque-Owned Enterprise (BUMas). This study concludes that the integration of prophetic values and modern management is capable of restoring the strategic role of mosques as centers of civilization and instruments of economic independence for the community.